Correcting PCR amplification errors in unique molecular identifiers to generate accurate numbers of sequencing molecules - Sun, J; Philpott, M; Loi, D; Li, S; Monteagudo-Mesas, P; Hoffman, G; Robson, J; Mehta, N; Gamble, V; Brown, T; Brown, T; Canzar, S; et al. (Springer Nature, 2024)
Unique molecular identifiers are random oligonucleotide sequences that remove PCR amplification biases. However, the impact that PCR associated sequencing errors have on the accuracy of generating absolute counts of RNA molecules is underappreciated. We show that PCR errors are a source of inaccuracy in both bulk and single-cell sequencing data, and synthesizing unique molecular identifiers using homotrimeric nucleotide blocks provides an error-correcting solution that allows absolute counting of sequenced molecules.